http://professores_inglês/sites/avaliação: avaliação de sites para/por professores de inglês - Palermo, Juliana Fridrich (2007)
This study aims at 1) describing and interpreting the evaluation of English teacher websites by English teachers, taken as a phenomenon of human experience, and 2) investigating these teachers representations of websites designed for them. To achieve these purposes, this study is founded on the concept of social representations (Moscovici, 1961/1976, 1976, 2003), on web design research proposed by Skaalid (1998) and Nielsen (1994, 2000, 2003, 2004, 2005), and on the discussion of instruments and website evaluation criteria (Nielsen, 2005; Schrock, 1998 e Maclachlan, 2002). The methodological approach chosen is the hermeneutic-phenomenological one (Ricoeur, 1986/2002; van Manen,1900; Freire, 2006). The research environment was the web, the virtual context in which the participant teachers and the researcher interacted through e-mail. The electronic medium was therefore used to send and receive three questionnaires, and their fifty ensuing messages. The results indicate that English teachers show a greater concern about website content, general organization and navigation. As for the phenomenon described and investigated, preferences, possibilities, usability and reflection were the four themes that structure the English teachers experience of evaluating sites designed for them. Moreover, the research results provide subsidies to begin thinking about the design of a website assessment instrument for English teachers